The effects of prolonged fasting, hibernation and leptin on in vivo lipid metabolism in mammals. - Reidy, Shannon Patricia. (University of Ottawa (Canada), 2000)
The main purpose of this thesis was to identify the changes that occur in m vim mammalian lipid metabolism during long-term fasting, arousal from hibernation, and following leptin treatment. Rabbits (Oryctolagus cuniculus) and woodchucks (Marmota monax) were fasted for one and two weeks, respectively, at room temperature and during different seasons. Woodchucks fasted in the summer lowered their energy expenditure and protein oxidation as soon as the fast was initiated. The woodchucks fasting in the spring did not, as their metabolic rate and protein utilization were already low, probably because in the wild they fast for extended periods of time following their final arousal from hibernation in the spring. The rabbits also exhibited metabolic depression and protein sparing with fasting although they used more protein and less lipid than the woodchucks. Using the continuous infusion method rates of triacylglycerol (TAG) hydrolysis (lipolysis), fatty acid (FA) mobilization and FA reesterification were measured on woodchucks that had just aroused from three months of hibernation. The contribution of TAGIFA substrate cycling to their total energy expenditure was extremely high (17%) Also, thermogenesis by this substrate cycle decreased the longer an animal had been aroused from hibernation, suggesting that this substrate cycle may be an important source of beat during arousal. Due to the high TAGIFA cycling rates, their lipolytic rate was also extremely high. Using the same methods, temporal changes in the rates of FA reesterification, lipolysis and lipid mobilization were measured in fasting rabbits. Their rates of lipolysis and FA mobilization initially doubled however, in the fix was prolonged, those rates decreased to pre-fasting levels. The metabolic depression induced by fasting probably accounted for the changes as less substrate was required for beta-oxidation. Reduced TAG/FA substrate cycling with long-term fasting accounted for a small amount of this metabolic depression (3%). The effects of leptin on TAG/FA recycling, lipolysis and FA mobilization were also investigated. In vivo leptin treatment caused significant increases in lipolytic rates and FA mobilization, and increased the relative contribution of lipid to the rabbit's total energy expenditure. The cycling rate of the TAG/FA substrate cycle was stimulated by leptin, contributing to 15% of the leptin-induced increase in energy expenditure. This showed that substrate cycling activation is a potent mechanism by which leptin can increase, metabolic thermogenesis.
Keywords: Biology, Animal Physiology.